2011
DOI: 10.1007/s00464-011-1912-x
|View full text |Cite
|
Sign up to set email alerts
|

Transumbilical laparoscopically assisted appendectomy in children: the results of a single-port, single-channel procedure

Abstract: The TULAA procedure is a preferable operation for acute appendicitis in children because it is simple and provides good cosmetic results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
44
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 35 publications
(43 reference statements)
4
44
0
Order By: Relevance
“…Length of Hospital stay, which is important for developing countries as it increases overall cost of treatment, was significantly shorter in laparoscopic group (p=0.015) with earlier bowel movements , start and tolerance to oral diet and early discharge from hospital. Thus my study is in alignment with several other researches 11,12 claiming shorter hospital stay with laparoscopic appendectomy than in open appendectomy. overcome psychological factors which may affect result of perception of pain by patients, only number of analgesic doses required were compared in both groups.…”
supporting
confidence: 87%
“…Length of Hospital stay, which is important for developing countries as it increases overall cost of treatment, was significantly shorter in laparoscopic group (p=0.015) with earlier bowel movements , start and tolerance to oral diet and early discharge from hospital. Thus my study is in alignment with several other researches 11,12 claiming shorter hospital stay with laparoscopic appendectomy than in open appendectomy. overcome psychological factors which may affect result of perception of pain by patients, only number of analgesic doses required were compared in both groups.…”
supporting
confidence: 87%
“…For example, a previous study reported the rate of conversion of LESS to conventional multiport appendectomy or the need for an additional transverse incision to range between 5 and 16.8% in pediatric cases. [13][14][15]. The transumbilical minimal incision approach does not require special equipment, or training such as that which is needed for laparoscopic surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Although criticized for technical difficulty and cost , the 3 ports "in" technique has been widely practiced and remains the gold standard, among techniques of laparoscopic appendectomy, due to its significant advantages [3]. However, it needs a complete surgical laparoscopy set in addition to a trained surgeon.…”
Section: Discussionmentioning
confidence: 99%
“…First reported by Valla [2]. Then by others like Ohno [3]. This technique concerned at the beginning only cases of uncomplicated appendicitis.…”
Section: Introductionmentioning
confidence: 99%